Assisted Fluid Management Software Guidance for Intraoperative Fluid Administration. (August 2021) - Maheshwari, Kamal; Malhotra, Gaurav; Bao, Xiaodong; Lahsaei, Peiman; Hand, William R.; Fleming, Neal W.; Ramsingh, Davinder; Treggiari, Miriam M.; Sessler, Daniel I.; Miller, Timothy E.; Butterfield, Ryan; Hipszer, Brian; et al.
Abstract : Background: Excessive or inadequate fluid administration causes complications, but despite this, fluid administration during noncardiac surgery is highly variable. Goal-directed management helps optimize the amount and timing of fluid administration; however, implementation is difficult because algorithms are complex. The authors therefore tested the performance of the Acumen Assisted Fluid Management software (Edwards Lifesciences, USA), which is designed to guide optimal intravenous fluid administration during surgery. Methods: In this multicenter, prospective, single-arm cohort evaluation, the authors enrolled 330 adults scheduled for moderate- to high-risk noncardiac surgery that required arterial catheter insertion and mechanical ventilation. Clinicians chose a fluid strategy based on a desired 10%, 15%, or 20% increase in stroke volume (SV) in response to a fluid bolus. Dedicated fluid management software prompted "test" or "recommended" boluses, and clinicians were free to initiate a "user" bolus of 100 to 500 ml of crystalloid or colloid. Clinicians were free to accept or decline the software prompts. The authors primarily compared the fraction of software-recommended boluses that produced suitable increases in SV to a 30% reference rate. On an exploratory basis, we compared responses to software-recommended and clinician-initiated boluses. Results: Four hundred twenty-four of 479 (89%) software-recommended fluid boluses and 508 of 592 (86%) clinician-initiated fluid boluses were analyzed per protocol. Of those, 66% (95% CI, 62 to 70%) of delivered fluid boluses recommended by the software resulted in desired increases in SV, compared with the 30% reference rate, whereas only 41% (95% CI, 38 to 44%) of clinician-initiated boluses did ( P < 0.0001). The mean ± SD increase in SV after boluses recommended by the software was 14.2 ± 13.9% versus 8.3 ± 12.1% ( P < 0.0001) for those initiated by clinicians. Conclusions: Fluid boluses recommended by the software resulted in desired SV increases more often, and with greater absolute SV increase, than clinician-initiated boluses. Automated assessment of fluid responsiveness may help clinicians optimize intraoperative fluid management during noncardiac surgery. Abstract : This multicenter, prospective study of investigational fluid management software in patients with an arterial catheter evaluated the fraction of software-recommended boluses producing a target increase in stroke volume. A higher percentage of software-recommended boluses met the target increase, compared to a historical reference rate and to clinicianinitiated boluses.Supplemental Digital Content is available in the text.